AR EduKids: Media Pembelajaran Pengenalan Hewan, Angka, dan Huruf Berbasis Augmented Reality untuk Anak Taman Kanak-Kanak - Dara Shaliha Happyananda Imani; Sutarman Sutarman (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
The learning process in Kindergarten (TK) still uses traditional media such as picture books and less interactive physical teaching aids, so children quickly get bored. Based on initial observations at Aba Jongke Islamic Kindergarten, Sleman, it was noted that more than half of the students lost focus after 10–15 minutes of learning activities. To address this problem, this study aims to design and develop an Augmented Reality (AR)-based learning application using the 4D Research and Development (R&D) model (Define, Design, Develop, Disseminate). The development process was validated by media and material experts, and tested on 1 teacher and 15 students as research subjects. The development results showed that the resulting AR application was able to increase student participation, increase learning motivation, and help them understand letters, numbers, and animals more quickly through a fun visual experience. In addition, teachers felt helped in delivering material because the class became more interactive and interesting. The final output of this study is an AR learning application for PAUD that is ready to be used as a supporting medium for learning activities in the classroom.